KAJIAN KETAHANAN AIR WS CITARUM UNTUK MENDUKUNG KETAHANAN PANGAN DI PROVINSI JAWA BARAT - aditia nata; Dayu Ariesta Kirana Sari; Taufiqur Rachman (Pranatacara Bhumandala: Jurnal Riset Planologi, 2023)
Water security is a very important aspect in the development of a region, because water is a primary need for humans. The aspect of water security is an important prerequisite in regional development. West Java Province as a national food barn has experienced quite rapid regional development. Concept to make a good water security is needed for the province. This study aims to identify existing water resource infrastructure in West Java province which is then linked to water security in West Java province. The results of this study identified that currently the condition of water resistance in West Java Province is in an unfavorable condition, especially at certain times. Based on the results of the GAP analysis, it shows that West Java Province is experiencing a water shortage, while the current infrastructure has not been able to function optimally to accommodate water. Even though the potential for river areas in West Java province is very abundant. In terms of quantity, water resistance in West Java province is actually quite good, but in some parts of the watersheds in West Java province there are some waters that are of poor quality, thereby reducing the availability of clean water for West Java province. The suggestions that can be made based on this research are adding water reservoirs and then maximizing the potential of the existing reservoirs, then ensuring the flow of water that is accommodated reaches residential areas with good quality.